2020
DOI: 10.1007/978-3-030-61244-3_1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Cognitive Difficulties Posed by SPARQL Query Constructs

Abstract: Paul (2020). A comparison of the cognitive difficulties posed by SPARQL query constructs. In: 22nd International Conference on Knowledge Engineering and Knowledge Management, Springer. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…An analysis of deviance, after controlling for expertise in the language being studied, showed a difference in performance between the two languages for this query (χ 2 (1) = 5.2024, p = 0.023). Warren and Mulholland have previously noted that questions with reverse predicates in SPARQL were answered less accurately and more slowly than analogous questions [4]. We suggest that the difference between SPARQL and Cypher may be due to the more intuitive method of representing predicate directionality in Cypher.…”
Section: Class Hierarchiesmentioning
confidence: 68%
See 1 more Smart Citation
“…An analysis of deviance, after controlling for expertise in the language being studied, showed a difference in performance between the two languages for this query (χ 2 (1) = 5.2024, p = 0.023). Warren and Mulholland have previously noted that questions with reverse predicates in SPARQL were answered less accurately and more slowly than analogous questions [4]. We suggest that the difference between SPARQL and Cypher may be due to the more intuitive method of representing predicate directionality in Cypher.…”
Section: Class Hierarchiesmentioning
confidence: 68%
“…Based on a readability metric, they concluded that Cypher was the most readable of the four languages. Warren and Mulholland [4] have investigated how accurately and rapidly users can reason about the main SPARQL features. Of relevance to this current study, they found that questions with reverse predicates were answered less accurately and more slowly than analogous questions with forward predicates.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, hundreds of gigabytes were collected over the years that would be extremely valuable if stored as a knowledge graph in an RDF triplestore. However, users usually feel intimidated to use Linked-Data as they are obliged to understand SPARQL and the underlying data structure [3]. In order to encourage these Bioscience researchers to adopt semantic web technologies in their field, it is essential to present a toolkit that fulfils their requirements to freely access the data store without the need to worry about its underlying technology.…”
Section: Introductionmentioning
confidence: 99%